Pendampingan Shalat Dhuha sebagai Upaya Pembinaan Karakter Siswa di SMKS Karsa Mulya Kota Palangka Raya - Dina Fahri Yani Safitri; Syahmidi Syahmidi; Sayid Ahmad Ramadhan (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Dhuha prayer mentoring as an effort to develop students' character at SMKS Karsa Mulya, Palangka Raya City through the Participatory Action Research (PAR) approach. This study aims to explore and understand the impact of Dhuha prayer practices on students' character development, including attitudes of discipline, responsibility, and spiritual values. Students involved in this program showed an increase in discipline and responsibility towards worship and schoolwork. In addition, Dhuha prayer activities also strengthen social bonds between students, creating a more harmonious learning environment. The results of the study showed that routine Dhuha prayer mentoring was able to increase students' religious awareness and improve their behavior in academic and social contexts. Students involved in this program showed an increase in discipline and responsibility towards worship and schoolwork.